2021
DOI: 10.2147/jir.s302832
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-29c-3p Promotes Intestinal Inflammation via Targeting Leukemia Inhibitory Factor in Ulcerative Colitis

Abstract: Background: Dysregulation of micro-RNAs (miRNAs) is profoundly linked to inflammatory bowel diseases (IBD), but little is known about the specific biological functions of miRNAs in IBD. This study sought to elucidate the effect and the underlying target of miR-29c-3p in ulcerative colitis (UC). Methods: The levels of miR-29c-3p and leukemia inhibitory factor (LIF) were measured in inflamed lesions of UC patients and dextran sulfate sodium (DSS)-induced colitis mice by quantitative real-time polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…miR-29c is also implicated in the positive regulation of NK cells cytotoxicity [ 13 ], and, through the negative regulation of tumor necrosis factor alpha-induced protein 3 (TNFAIP3), it also modulates the activity of NF-kappa B in T cells [ 14 ]. Interestingly, miR-29c is upregulated in experimental models of sepsis [ 15 ] and ulcerative colitis [ 16 ], thus confirming its proinflammatory activity. Moreover, miR-29c seems to also display an antifibrotic action [ 17 ] through different mechanisms, such as the modulation of the Fer expression [ 18 ], and the blockade of the macrophage migration inhibitory factor [ 19 ].…”
Section: Discussionmentioning
confidence: 97%
“…miR-29c is also implicated in the positive regulation of NK cells cytotoxicity [ 13 ], and, through the negative regulation of tumor necrosis factor alpha-induced protein 3 (TNFAIP3), it also modulates the activity of NF-kappa B in T cells [ 14 ]. Interestingly, miR-29c is upregulated in experimental models of sepsis [ 15 ] and ulcerative colitis [ 16 ], thus confirming its proinflammatory activity. Moreover, miR-29c seems to also display an antifibrotic action [ 17 ] through different mechanisms, such as the modulation of the Fer expression [ 18 ], and the blockade of the macrophage migration inhibitory factor [ 19 ].…”
Section: Discussionmentioning
confidence: 97%
“…Another miRNA considered in the context of the PCOS pathomechanism, miR-29c-3p, shows opposite effects with respect to inflammation, depending on the tissue and signaling pathways used. Hence, miR-29c-3p may promote intestinal inflammation by targeting leukemia inhibitory factor (LIF) in ulcerative colitis and, through targeting the transcription factor forkhead box protein O3 (FOXO3A), may ameliorate inflammatory damage of cells by NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome inhibition [ 197 , 198 , 199 ]. Moreover, miR-29c-3p participates in insulin function by targeting FOXO3A.…”
Section: Epigenetic Regulation Of Insulin Resistance and Inflammatory...mentioning
confidence: 99%
“…Studies have found that many miRNAs are involved in the development of many diseases by post-translational regulation [ 15 , 16 ]. Recently, a number of studies regarding miRNAs in UC have reported a critical role of miRNAs during the development of UC, such as miR-182-5p [ 17 ] and miR-29c-3p [ 18 ]. Additionally, miRNA-142-5p is involved in cervical cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%